CARDIAC SURGERYEarly and long-term results of cardiosurgical treatment of coronary artery disease and aortic stenosis in patients over 80 years old - Budniak, Wiktor; Buczkowski, Piotr; Perek, Bartłomiej; Katyńska, Izabela; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Background: In recent years, patients over 80 years of age have been a growing group of individuals referred to cardiac surgeons. They pose a serious challenge and usually require a multidisciplinary approach. Aim : The aim of this study was to evaluate the early and late outcomes of cardiosurgical treatment of patients over 80 years of age suffering from coronary artery disease and aortic stenosis. Material and methods: The study involved 96 patients aged over 80 years treated between January, 2004 and December, 2012. The mortality and morbidity in the early postoperative period, as well as throughout the follow-up period, were analyzed. Results : The majority of patients underwent isolated coronary artery bypass grafting (CABG) (58.3%; Group I), while 29.2% of them underwent an isolated aortic valve replacement (AVR) (Group II). Combined procedures (CABG + AVR) were carried out in 12.5% of patients (Group III). The mean operational risk calculated according to the logistic EuroSCORE was 11.6%, 11.9%, and 9.5%, respectively in Group I, Group II and in Group III. In the early postoperative period, 4 patients died (all from Group I). The 30-day mortality rate was 4.2% and the morbidity rate was 56.3%. During the post-discharge follow-up period that lasted from 1 to 100 months, 4 patients died (2 from Group I and 2 from Group III). The 2-year probability of survival was 91.9 ± 3.0%. During the last follow-up clinical assessment, half of the patients were asymptomatic. Conclusions : The perioperative mortality of the patients is acceptably and markedly lower than that predicted by the logistic EuroSCORE calculator. However, the complication rate, particularly in the early postoperative period, is relatively high.